Moral and ethical aspects of organ donation for transplantation – catechism project - B. I. Yaremin; S. Yu. Pushkin; A. S. Navasardyan; A. A. Selyutin; K. K. Gubarev; V. E. Alexandrova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The moral and ethical aspects of organ donation for transplantation constitute a new section of the doctor's activity. The correct and motivated awareness of the answers to the main questions that may arise from members of the public, patients, members of their families, medical personnel, undoubtedly, is within the competence of the doctor. This work is devoted to the analysis of existing approaches to answering the main questions arising around the activity of preserving the organs of the deceased for transplantation. The work was done in the format of a catechism, questions and the answers offered to them. Answers are given as one of the options.